Meaning Construction for Biodynamic Osteopathy Terms in Translation Practice - Kalinina, Irina (Taikomoji kalbotyra, 2021)
This article belongs to the interface of terminology and translation studies and aims to describe the principles of meaning construction in the translation of field-specific terms in biodynamic osteopathy. The central problem of the study presented in this paper deals with identification and analysis of measurable components of meaning of terminological units. The data for the study comprises a corpus of 210 English terms in the field of biodynamic osteopathy translated into French, Italian, Russian and Latvian. Following the analysis of the meanings of the terms through their contextual uses, it is possible to assess other factors that contribute to the content of these units.Methodologically, we built a definition for each term based on its context. Next, we investigated the notion of semantic resonance that is relevant for terminological units derived from general language. The study suggests that even in the field of neology where the concepts are borrowed together with the terms, resonance can vary from one language to another, which, as a consequence, highlights the problem of cross-linguistic equivalence in the translation of texts in this field.
Keywords: terminology; meaning; translation; resonance; field-specific language